Arts and myths [videorecording (DVD)] - Truffault, Philippe; Portron, Jean-Loïc (Arte France Développement : Arte Video ; Distributed by Facets Video, 2006)
Introduces us to the 'first arts' and to major artistic pieces from Africa, Oceania, South America, and Asia. The films offers insight into the creation of the pieces, their uses, their history, and more.